(untitled) (BIRDEM Medical Journal, 2025)
Background: Haemorrhoidal disease (HD) is the most common anorectal disease affecting millions of people around the world and represents a major medical and socioeconomic problem, severely affecting patients’ quality of life. This study aimed to compare the early outcome of stapled haemorrhoidopexy versus open haemorrhoidectomy for treatment of second and third degree haemorrhoids. Methods: In this study, adult patients who presented to the general surgery outpatient clinics in BIRDEM General Hospital with symptomatic second and third degree hemorrhoid along with patients who agreed to continue follow[1] up for 6 weeks were included. This study was carried out from May 2023 to October 2024 after ethical clearance from Intitutional reiview board of BIRDEM General Hospital. Patients follow up was on the first post operative day, after 1 week and after 6 weeks. This was a quasi experimental study, sampling method was convenience sampling and patients were treated by either stapled haemorrhoidopexy (n=32) or open haemorrhoidectomy (n=32). The total sample size was 64. Data were collected by using a questionnaire for the study by researcher herself. Data processing and analysis were done using SPSS (statistical package for social sciences), version 26. Results: To evaluate the outcome of stapled haemorrhoidopexy (SH) and open haemorrhoidectomy (OH), 64 patients were compared for age, comorbidities and results. The average operation duration for OH was much lower (27.6 ± 5.6 minutes) than for SH (34.0 ± 6.12 minutes). In the SH group, 96.9% (31 patients) had intraoperative bleeding under 30 ml, compared to 87.5% (28 patients) in the OH group, although this difference was not statistically significant (p=0.355). The SH group had significantly lower pain scores on the 1st and 7th postoperative days (3.97 ± 0.47) and (2.19 ± 0.78) compared to the OH group (4.84 ± 0.98 and 2.94 ± 0.87, respectively) (p=0.001). All OH patients needed sitz bath for more than 7 days, while only 6.3% of SH patients did (p=0.001). The SH group had no wound infections on the 7th postoperative day, compared to 12.5% in the OH group (p=0.162). The SH group had a shorter hospital stay (1.09 ± 0.2 days) than the OH group (1.23 ± 0.4 days), however the difference was not statistically significant (p=0.182). The SH group returned to normal activities significantly earlier (2.63 ± 0.8 days) than the OH group (4.28 ± 1.2 days) (p=0.001). SH patients were 37.5% satisfied and rated as excellent with their findings, compared to 9.4% of OH patients. Conclusion: Overall, stapled haemorrhoidopexy demonstrated advantages in terms of postoperative pain, recovery time, and patient satisfaction, whereas open haemorrhoidectomy showed shorter operative times. BIRDEM Med J 2025; 15(3): 103-110